Opposing action of photosystem II assembly factors RBD1 and HCF136 underlies light-regulated psbA translation in plant chloroplasts - Margarita Rojas; Rosalind Williams-Carrier; Prakitchai Chotewutmontri; Susan Belcher; Emily Boyce; Alice Barkan (Proceedings of the National Academy of Sciences, 2025)
The D1 subunit of photosystem II (PSII) is subject to light-induced damage. In plants, D1 photodamage activates translation of chloroplast psbA mRNA encoding D1, providing D1 for PSII repair. Three D1 assembly factors have been implicated in the regulatory mechanism: HCF244 and RBD1 activate psbA translation, whereas HCF136 represses psbA translation in the dark. To clarify the regulatory circuit, we analyzed psbA ribosome occupancy in dark-adapted and illuminated rbd1 and rbd1;hcf136 double mutants in Arabidopsis and in Zm- hcf244 and Zm- hcf244; Zm- hcf136 double mutants in maize. The results show that RBD1 is required for light-induced psbA translation but has only a small effect on psbA ribosome occupancy in the dark. RBD1 is not required for psbA translation when HCF136 is absent, indicating that RBD1 activates psbA translation in the light by inhibiting HCF136’s repressive effect. By contrast, HCF244 is required to recruit ribosomes to psbA mRNA in light, dark, and in the absence of HCF136. We demonstrate further that HCF244 is not required for the translational activator HCF173 to bind the psbA 5’UTR. These results show that RBD1 is central to the perception of the D1 photodamage that triggers D1 synthesis and that it activates psbA translation by relieving repression by an HCF136-dependent assembly intermediate. HCF244 activates downstream of those events without impacting HCF173’s binding to psbA mRNA. The results implicate a feature of nascent D1 that is affected by both HCF136 and RBD1 as the signal that reports D1 photodamage to regulate psbA translation rate as needed for PSII repair.